The impact of political factors on the profitability and market share of Syrian insurance companies (Journal of Hama University, 2024)
This study examined political factors and their impact on the profitability of insurance companies, given that the insurance sector is one of the sectors that support the local economy of any country, given the vitality that this sector enjoys in the process of accumulating capital, saving and investment, through a questionnaire that was distributed to a number of workers in the insurance sector. It included questions about the association of insurance allowances and coverage with the security and political situations and the resulting reluctance of companies to accept insurance for contracts with large coverages as a result of exchange rate changes, and about the impact of company branches and activities on security events and political changes. The questionnaire was also analyzed using the SPSS program and using appropriate statistical tests as a test. Student and simple linear regression test.Through this study, we found that there is a statistically significant impact of political factors on the profitability of insurance companies